Contribution of Dopamine D1/5 Receptor Modulation of Post-Spike/Burst Afterhyperpolarization to Enhance Neuronal Excitability of Layer V Pyramidal Neurons in Prepubertal Rat Prefrontal Cortex - Yi, Feng (Public Library of Science, 2013)
Dopamine (DA) receptors in the prefrontal cortex (PFC) modulate both synaptic and intrinsic plasticity that may contribute to cognitive processing. However, the ionic basis underlying DA actions to enhance neuronal plasticity in PFC remains ill-defined. Using whole-cell patch-clamp recordings in layer V-VI pyramidal cells in prepubertal rat PFC, we showed that DA, via activation of D1/5, but not D2/3/4, receptors suppress a Ca(2+)-dependent, apamin-sensitive K(+) channel that mediates post-spike/burst afterhyperpolarization (AHP) to enhance neuronal excitability of PFC neurons. This inhibition is not dependent on HCN channels. The D1/5 receptor activation also enhanced an afterdepolarizing potential (ADP) that follows the AHP. Additional single-spike analyses revealed that DA or D1/5 receptor activation suppressed the apamin-sensitive post-spike mAHP, further contributing to the increase in evoked spike firing to enhance the neuronal excitability. Taken together, the D1/5 receptor modulates intrinsic mechanisms that amplify a long depolarizing input to sustain spike firing outputs in pyramidal PFC neurons.